UV-curable adhesive composition, adhesive film including the same, polarizing film including the same, and display device including the polarizing film
The UV-curable adhesive composition with specific components addresses the challenge of achieving consistent adhesive strength on diverse substrates, improving productivity and cost-effectiveness in polarizing plate applications.
Patent Information
- Application Number
- JP2023549660
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-11-05
- Filing Date
- 2022-10-25
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-10-25
AI Technical Summary
Conventional adhesives used in polarizing plates face challenges in achieving sufficient adhesive strength on both moisture-permeable and non-moisture-permeable substrates, leading to increased costs and decreased productivity due to the need for multiple adhesive types and frequent changes.
A UV-curable adhesive composition comprising monofunctional acrylate, polyfunctional acrylate, silane coupling agent, cationic initiator, and photosensitizer, with specific ratios and epoxy groups, ensuring excellent adhesive strength regardless of substrate type.
The adhesive composition provides robust adhesion to both moisture-permeable and non-moisture-permeable substrates, enhancing productivity and reducing costs by allowing a single adhesive type to be used across different materials.
Smart Images

Figure 0007618302000003 
Figure 0007618302000001 
Figure 0007618302000002
Abstract
Description
[Technical field]
[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2021-0151166, filed with the Korean Intellectual Property Office on November 5, 2021, the entire contents of which are incorporated herein by reference.
[0002] The present application relates to a UV-curable adhesive composition, an adhesive film containing the same, a polarizing film containing the same, and a display device containing the polarizing film. [Background technology]
[0003] In recent years, with the development of optical technology, display devices using various methods such as plasma display panels (PDPs) replacing conventional cathode ray tubes, liquid crystal displays (LCDs), and organic light emitting diodes (OLEDs) have been proposed and are on the market. Recently, the characteristics required for such display devices have become more advanced, and therefore the characteristics required for peripheral components such as optical films and polarizing films applied to display devices have also become more advanced.
[0004] Liquid crystal display devices are used in various display devices such as TVs, mobile phones, car navigation systems, portable game machines, and other portable terminals, taking advantage of their features such as low power consumption, low voltage operation, light weight, and thinness. Examples of such liquid crystal display devices include VA (Vertical Alignment) mode, IPS (In-Plane Switching) mode, FFS (Fringe Field Switching) mode, and OCB (Optical Compensated Bend) mode. These liquid crystal display devices are generally composed of a backlight, a liquid crystal cell containing liquid crystal molecules sandwiched between two electrodes, and two polarizing plates provided on both sides of the liquid crystal cell, and when a voltage is applied, the transmitted light can be controlled by changing the optical refractive index of the liquid crystal molecules to display an image. In these modes, the light absorption axes of the two polarizing films are arranged at 90° to each other so that no light is transmitted when no voltage is applied to the liquid crystal cell (when no voltage is applied). Such a liquid crystal display device that displays black when no voltage is applied and white when voltage is applied is called a normally black type.
[0005] Recently, efforts are being made in the polarizing plate market to minimize defects and increase product productivity. Conventionally, moisture-permeable substrates (WVRT>200g / m2) have been used as protective substrates for polarizing plates. 2 In the past, polarizing plates were manufactured using water-based adhesives and TAC (Triacetyl cellulos), which is a low-temperature polymer that is used for polarizing plates. However, nowadays, polarizing plates are manufactured using non-moisture-permeable substrates (WVRT<200g / m2) such as PET, acrylic, or COP films. 2 ·day) is also commonly used.
[0006] When a conventional moisture-permeable protective substrate was used, it was possible to attach the upper and lower protective substrates of a polarizing plate with one type of adhesive. However, in recent products that use not only a moisture-permeable substrate alone but also a moisture-permeable substrate and a moisture-non-permeable substrate simultaneously, there is a problem that it is difficult to realize sufficient adhesive strength as a water-based adhesive when using only one adhesive.
[0007] That is, an adhesive composition that has good adhesion to a moisture-permeable protective substrate is poor at adhering to a moisture-non-permeable substrate, and vice versa. Therefore, as various substrate characteristics are currently being applied, adhesives must also differ depending on the substrate. Therefore, there is a need to improve the adhesive margin of adhesives and develop adhesives that can be applied to both moisture-permeable and moisture-non-permeable substrates.
[0008] Currently, in order to solve these problems, it is common to use separate adhesives for the upper and lower surfaces of polarizing plates according to the moisture permeable and moisture non-permeable substrates. However, although using separate adhesives for the moisture permeable and moisture non-permeable substrates has the advantage of improving adhesion, it is necessary to replace the adhesive every time depending on the product group, which causes problems such as increased costs due to the replacement of the adhesive and reduced productivity of the product.
[0009] A single change of adhesive applied to polarizing film generally results in about 3 to 6 hours of floating, plus additional time for path changes due to wet / dry changes, draining / filling of adhesive, changing mesh rolls, cleaning / washing of pipes, etc.
[0010] Therefore, it is necessary to develop an adhesive layer that can be applied to polarizing plates and that can be used regardless of the type of protective substrate (moisture-permeable substrate or moisture-non-permeable substrate) attached to the polarizing plate in accordance with the currently applied product group. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Patent Publication No. 6536022 Summary of the Invention [Problem to be solved by the invention]
[0012] The present application relates to a UV-curable adhesive composition, an adhesive film containing the same, a polarizing film containing the same, and a display device containing the polarizing film. [Means for solving the problem]
[0013] One embodiment of the present specification provides a UV-curable adhesive composition comprising a monofunctional acrylate, a polyfunctional acrylate, a silane coupling agent, a cationic initiator, and a photosensitizer, the silane coupling agent being contained in an amount of 15 parts by weight or more based on 100 parts by weight of the monomer comprising the monofunctional acrylate, the polyfunctional acrylate, and the silane coupling agent, the polyfunctional acrylate comprising an acrylate having two functional groups and an acrylate having three or more functional groups, the polyfunctional acrylate comprising 70 parts by weight or more of the acrylate having two functional groups based on 100 parts by weight of the polyfunctional acrylate, the silane coupling agent having one or more epoxy groups in its molecule, and at least one of the epoxy groups being an alicyclic epoxy group or a non-alicyclic epoxy group.
[0014] In still another embodiment, an adhesive film is provided, which comprises the UV-curable adhesive composition according to the present application or a cured product thereof.
[0015] In still another embodiment, a polarizer; a first adhesive layer and a second adhesive layer provided on both sides of the polarizer; 2 a transparent protective film having a moisture permeability of 150 g / m2 or less; and a second adhesive layer provided on the surface opposite to the surface in contact with the polarizer. 2 a transparent protective film having a shelf life of 24 hours or more; wherein the first adhesive layer and the second adhesive layer are the adhesive films according to the present application.
[0016] Finally, a display device is provided that includes the polarizing film of the present application. Effect of the Invention
[0017] A UV curable adhesive composition according to one embodiment of the present invention necessarily contains a monofunctional acrylate, a polyfunctional acrylate, a silane coupling agent, a cationic initiator, and a photosensitizer. In particular, the silane coupling agent is contained in an amount of 15 parts by weight or more based on 100 parts by weight of the monomer, and the silane coupling agent has one or more epoxy groups in the molecule, at least one of which has an alicyclic epoxy group or a non-alicyclic epoxy group, and has the characteristic of exhibiting excellent adhesive strength regardless of whether the substrate to be bonded is moisture permeable or non-moisture permeable.
[0018] Furthermore, the polyfunctional acrylate contained in the film contains two types of acrylates, and among these, the acrylate containing two functional groups contains a specific content and specific functional groups, which can improve the wettability of the polarizing plate or substrate and can have excellent adhesive strength regardless of the protective substrate used.
[0019] In addition, the UV curable adhesive composition according to one embodiment of the present invention contains a specific amount of monofunctional acrylate and polyfunctional acrylate, and reduces the surface energy of the adhesive layer containing the same, and has excellent wetting properties on a polarizing plate or substrate without inducing bubbles during processing, and has the characteristic of having excellent apparent quality of a polarizing film containing the same. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a diagram showing a laminate structure of a polarizing film according to one embodiment of the present specification. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Before describing the present invention, some terms will first be defined.
[0022] In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, not excluding other components, unless specifically stated to the contrary.
[0023] In this specification, "p to q" means a range of "not less than p and not more than q."
[0024] As used herein, acrylate is meant to include both acrylates and (meth)acrylates.
[0025] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings in order to enable those skilled in the art to easily practice the present invention. However, the present invention may be embodied in many different forms and should not be construed as limited to the disclosed embodiments.
[0026] One embodiment of the present specification provides a UV-curable adhesive composition comprising a monofunctional acrylate, a polyfunctional acrylate, a silane coupling agent, a cationic initiator, and a photosensitizer, the silane coupling agent being contained in an amount of 15 parts by weight or more based on 100 parts by weight of the monomer comprising the monofunctional acrylate, the polyfunctional acrylate, and the silane coupling agent, the polyfunctional acrylate comprising an acrylate comprising two functional groups and an acrylate comprising three or more functional groups, the polyfunctional acrylate comprising 70 parts by weight or more of the acrylate comprising two functional groups based on 100 parts by weight of the polyfunctional acrylate, the silane coupling agent having one or more epoxy groups in its molecule, and at least one of the epoxy groups being an alicyclic epoxy group or a non-alicyclic epoxy group.
[0027] A UV curable adhesive composition according to one embodiment of the present invention necessarily contains a monofunctional acrylate, a polyfunctional acrylate, a silane coupling agent, a cationic initiator, and a photosensitizer. In particular, the silane coupling agent is contained in an amount of 15 parts by weight or more based on 100 parts by weight of the monomer, and the silane coupling agent has one or more epoxy groups in the molecule, at least one of which has an alicyclic epoxy group or a non-alicyclic epoxy group, and has the characteristic of exhibiting excellent adhesive strength regardless of whether the substrate to be bonded is moisture permeable or non-moisture permeable.
[0028] The characteristics of each of the adhesive compositions included in this application are described below.
[0029] In one embodiment of the present application, the monofunctional acrylate may be an alkyl(meth)acrylate. In the alkyl(meth)acrylate, the alkyl group may be linear or branched as long as it has 3 or more carbon atoms. Specific examples of the alkyl(meth)acrylate include methyl(meth)acrylate, ethyl(meth)acrylate, isopropyl(meth)acrylate, butyl(meth)acrylate, isobutyl(meth)acrylate, and tert-butyl(meth)acrylate. Also usable as the single polymerizable monomer may be alkyl (meth)acrylates having a larger number of carbon atoms in the alkyl group, such as 2-ethylhexyl (meth)acrylate, aralkyl (meth)acrylates, such as benzyl (meth)acrylate, (meth)acrylates of terpene alcohols, such as isobornyl (meth)acrylate, (meth)acrylates having a tetrahydrofurfuryl structure, such as tetrahydrofurfuryl (meth)acrylate, (meth)acrylates having a cycloalkyl group in the alkyl group moiety, such as cyclohexylmethyl methacrylate, dicyclopentanyl acrylate, and 1,4-cyclohexanedimethanol monoacrylate, aminoalkyl (meth)acrylates, such as N,N-dimethylaminoethyl (meth)acrylate, and (meth)acrylates having an ether bond in the alcohol moiety, such as 2-phenoxyethyl (meth)acrylate, ethyl carbitol (meth)acrylate, and phenoxypolyethylene glycol (meth)acrylate.
[0030] Also, monofunctional (meth)acrylates having a hydroxyl group at the alcohol moiety or monofunctional (meth)acrylates having a carboxyl group at the alcohol moiety may be used. Specific examples of monofunctional (meth)acrylates having a hydroxyl group at the alcohol moiety include 2-hydroxyethyl (meth)acrylate, 2- or 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, trimethylolpropane mono(meth)acrylate, and pentaerythritol mono(meth)acrylate. Specific examples of monofunctional (meth)acrylates having a carboxy group in the alcohol moiety include 2-carboxyethyl (meth)acrylate, 1-[2-(meth)acryloyloxyethyl]phthalic acid, 1-[2-(meth)acryloyloxyethyl]hexahydrophthalic acid, 1-[2-(meth)acryloyloxyethyl]succinic acid, and 4-[2-(meth)acryloyloxyethyl]trimellitic acid.
[0031] In yet another embodiment, the monofunctional acrylate may be 4-hydroxybutyl acrylate (4-HBA).
[0032] The monofunctional acrylate means an acrylate having one functional group in the molecule, and the functional group may be an acrylate group.
[0033] In one embodiment of the present application, the monofunctional acrylate may be used alone.
[0034] In one embodiment of the present application, two types of the monofunctional acrylates may be used.
[0035] In one embodiment of the present application, the multifunctional acrylate means an acrylate having two or more functional groups in the molecule, and the functional groups may be acrylate groups.
[0036] In one embodiment of the present application, the number of functional groups of the polyfunctional acrylate may be 2 or more and 10 or less, preferably 2 or more and 6 or less, and more preferably 2 or more and 5 or less.
[0037] When the polyfunctional acrylate has two functional groups, it may be expressed differently as a bifunctional acrylate, and when it has three functional groups, it may be expressed differently as a trifunctional acrylate.
[0038] In one embodiment of the present application, representative examples of bifunctional acrylates include alkylene glycol di(meth)acrylates, polyoxyalkylene glycol di(meth)acrylates, di(meth)acrylates of halogen-substituted alkylene glycols, di(meth)acrylates of aliphatic polyols, di(meth)acrylates of hydrogenated dicyclopentadiene or tricyclodecane dialkanol, di(meth)acrylates of dioxane glycol or dioxane dialkanol, di(meth)acrylates of alkylene oxide adducts of bisphenol A or bisphenol F, and epoxy di(meth)acrylates of bisphenol A or bisphenol F.
[0039] In one embodiment of the present application, more specific examples of the bifunctional acrylate include ethylene glycol di(meth)acrylate, 1,3-butanediol (meth)acrylate, 1,4-butanediol (meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, pentaerythritol di(meth)acrylate, ditrimethylolpropane di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, acrylate, di(meth)acrylate of hydroxypivalic acid neopentyl glycol ester, 2,2-bis[4-{2-(2-(meth)acryloyloxyethoxy)ethoxy}phenyl]propane, 2,2-bis[4-{2-(2-(meth)acryloyloxyethoxy)ethoxy}cyclohexyl]propane, hydrogenated dicyclopentadienyl di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, 1,3-dicyclopentadienyl di(meth)acrylate, Examples include dioxane-2,5-diyl di(meth)acrylate (also known as dioxane glycol di(meth)acrylate), the di(meth)acrylate of acetalized hydroxypivalinaldehyde and trimethylolpropane (chemical name: 2-(2-hydroxy-1,1-dimethylethyl)-5-ethyl-5-hydroxymethyl-1,3-dioxane), and the di(meth)acrylate of 1,3,5-tris(2-hydroxyethyl)isocyanurate.
[0040] In one embodiment of the present application, a representative example of the polyfunctional acrylate having three or more functional groups is a poly(meth)acrylate of aliphatic polyol having three or more functional groups. Specific examples thereof include glycerin tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, glycerin ethylene oxide modified tri(meth)acrylate, and ethylene oxide modified trimethylolpropane tri(meth)acrylate.
[0041] On the other hand, the acrylate oligomer includes a urethane (meth)acrylate oligomer, a polyester (meth)acrylate oligomer, an epoxy (meth)acrylate oligomer, and the like.
[0042] In one embodiment of the present application, the multifunctional acrylate may be HYDROXYPIVALIC ACID NEOPENTYLGLYCOL DIACRYLATE; or Tris(2-hydroxy ethyl)isocyanurate triacrylate.
[0043] In one embodiment of the present application, two types of the multifunctional acrylate may be used.
[0044] In one embodiment of the present application, there is provided a UV-curable adhesive composition in which the multifunctional acrylate includes an acrylate having two functional groups and an acrylate having three or more functional groups, and the UV-curable adhesive composition includes 70 parts by weight or more of the acrylate having two functional groups based on 100 parts by weight of the multifunctional acrylate.
[0045] In yet another embodiment, the polyfunctional acrylate includes an acrylate having two functional groups and an acrylate having three or more functional groups, and may include the acrylate having two functional groups in an amount of 70 parts by weight or more, preferably 70.5 parts by weight or more, more preferably 71 parts by weight or more, based on 100 parts by weight of the polyfunctional acrylate, and may include 90 parts by weight or less, preferably 85 parts by weight or less, more preferably 80 parts by weight or less, and most preferably less than 80 parts by weight.
[0046] In yet another embodiment, the multifunctional acrylate includes an acrylate having two functional groups and an acrylate having three or more functional groups, and may include 70 parts by weight or more and 80 parts by weight or less of the acrylate having two functional groups based on 100 parts by weight of the multifunctional acrylate.
[0047] In one embodiment of the present application, a UV-curable adhesive composition is provided, wherein the difunctional acrylate comprises a hydroxypivalic acid group.
[0048] The UV-curable adhesive composition according to the present application contains two types of acrylates as the polyfunctional acrylate, and among them, the acrylate containing two functional groups contains the above-mentioned content and specific functional groups, thereby improving the wettability of the polarizing plate or substrate and providing excellent adhesion regardless of the protective substrate used.
[0049] In one embodiment of the present application, the monomer may include a monofunctional acrylate, a polyfunctional acrylate, and a silane coupling agent, and may also include other additives.
[0050] In one embodiment of the present application, there is provided a UV-curable adhesive composition comprising, based on 100 parts by weight of the monomer, 1 part by weight or more and 30 parts by weight or less of the monofunctional acrylate and 40 parts by weight or more and 90 parts by weight or less of the polyfunctional acrylate.
[0051] In another embodiment, the monofunctional acrylate may be present in an amount of 1 part by weight or more and 30 parts by weight or less, preferably 5 parts by weight or more and 30 parts by weight or less, and more preferably 10 parts by weight or more and 30 parts by weight or less, based on 100 parts by weight of the monomer.
[0052] In another embodiment, the amount of the polyfunctional acrylate may be 40 parts by weight or more and 90 parts by weight or less, preferably 45 parts by weight or more and 90 parts by weight or less, and more preferably 45 parts by weight or more and 85 parts by weight or less, based on 100 parts by weight of the monomer.
[0053] As described above, by including the monofunctional acrylate and polyfunctional acrylate in the UV curable adhesive composition in the above range, the adhesive strength is not reduced even when a moisture permeable or non-moisture permeable substrate is laminated on both sides of a polarizing plate, and the adhesive composition has the characteristic of exhibiting excellent adhesive strength. Furthermore, the adhesive composition has the characteristic of exhibiting excellent wettability of the substrate after moisture permeation.
[0054] In one embodiment of the present application, the UV curable adhesive composition may contain a silane coupling agent.
[0055] In one embodiment of the present application, the silane coupling agent has one or more epoxy groups in the molecule, and at least one of the epoxy groups may be an alicyclic epoxy group or a non-alicyclic epoxy group.
[0056] In still another embodiment, the silane coupling agent may have one or more epoxy groups in the molecule, and at least one of the epoxy groups may be an alicyclic epoxy group.
[0057] In still another embodiment, the silane coupling agent may have one or more epoxy groups in the molecule, and at least one of the epoxy groups may be a non-alicyclic epoxy group.
[0058] In still another embodiment, the silane coupling agent has one epoxy group in the molecule, and the epoxy group may be a non-alicyclic epoxy group.
[0059] In still another embodiment, the silane coupling agent has one epoxy group in the molecule, and the epoxy group may be an alicyclic epoxy group.
[0060] In particular, in one embodiment of the present application, the silane coupling agent has one epoxy group in the molecule, and when the epoxy group is a non-alicyclic epoxy group, there is no significant change in adhesive properties compared to when an alicyclic epoxy group is used, but the initial feasibilty evaluation may show very superior characteristics compared to when an alicyclic epoxy group is used.
[0061] In one embodiment of the present application, the silane coupling agent is not limited to this as long as it has an epoxy group, but may specifically be 3-glycidoxypropyltrimethoxysilane.
[0062] The present application is characterized in that the UV-curable adhesive composition contains a silane coupling agent having at least one epoxy group, and in particular, the silane coupling agent is contained in an amount of 15 parts by weight or more based on 100 parts by weight of the monomer.
[0063] In another embodiment, based on 100 parts by weight of the monomer, the silane coupling agent may be 15 parts by weight or more, 50 parts by weight or less, preferably 45 parts by weight or less, more preferably 35 parts by weight or less, and most preferably 30 parts by weight or less.
[0064] The present application is characterized in that the UV curable adhesive composition contains specific amounts of polyfunctional and monofunctional acrylates and the silane coupling agent having at least one epoxy group in the above amounts, and is contained in a larger amount than that generally used in the form of an additive in an adhesive layer.
[0065] The silane coupling agent according to the present application not only functions as a general coupling agent, but also serves as an additive for increasing the adhesive strength of the composition. It has been confirmed that the adhesive layer according to the present invention has good effect when it is contained in an amount of at least 15 parts by weight based on 100 parts by weight of the monomer.
[0066] That is, by containing the silane coupling agent according to the present application in the above content, the adhesive strength is excellent even when various types of protective substrates such as moisture permeable / non-moisture permeable, moisture permeable / moisture permeable, and moisture non-permeable / non-moisture permeable are used on the upper and lower parts of the polarizing plate, and the wettability on the polarizing plate is also excellent, resulting in a polarizing film with excellent appearance.
[0067] In one embodiment of the present application, the UV curable adhesive composition may include a cationic initiator and a photosensitizer.
[0068] In the present application, the cationic initiator may be any one capable of initiating the polymerization of the polymerizable monomer and the polymerizable polyfunctional acrylate by irradiation with ultraviolet light, and may be any one known in the art. Specific examples of the photoradical polymerization initiator include acetophenone-based initiators such as acetophenone, 3-methylacetophenone, benzyl dimethyl ketal, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, 2-methyl-1-[4-(methylthio)phenyl-2-morpholino-propan-1-one, and 2-hydroxy-2-methyl-1-phenylpropan-1-one; benzophenone-based initiators such as benzophenone, 4-chlorobenzophenone, and 4,4'-diaminobenzophenone; benzoin ether-based initiators such as benzoin propyl ether and benzoin ethyl ether; thioxanthone-based initiators such as 4-isopropylthioxanthone; and others such as xanthone, fluorenone, camphorquinone, benzaldehyde, and anthraquinone.
[0069] In one embodiment of the present application, the cationic initiator refers to a compound that generates cationic species or Lewis acids upon irradiation with active energy rays such as ultraviolet rays, and acts on a cationic polymerizable group such as an epoxy group to initiate a cationic polymerization reaction.
[0070] In one embodiment of the present application, the cationic initiator may comprise a sulfonium salt or an iodonium salt.
[0071] In one embodiment of the present application, the cationic initiator is for promoting polymerization and improving the curing rate, and as the cationic polymerization initiator, any cationic initiator commonly used in the art may be used without limitation.
[0072] In one embodiment of the present application, the photosensitizer is added to improve the reactivity of radical polymerization, and the mechanical strength and adhesiveness of the adhesive layer can be improved. The photosensitizer may be any compound that has a maximum absorption at a wavelength longer than 380 nm, and examples of the photosensitizer include carbonyl compounds, organic sulfur compounds, persulfur compounds, redox compounds, azo and diazo compounds, halogen compounds, anthracene compounds, and photoreducible dyes.
[0073] In one embodiment of the present application, there is provided a UV-curable adhesive composition comprising, based on 100 parts by weight of the UV-curable adhesive composition, 0.1 parts by weight or more and 5 parts by weight or less of the cationic initiator and 0.1 parts by weight or more and 5 parts by weight or less of the photosensitizer.
[0074] In another embodiment, the cationic initiator may be contained in an amount of 0.1 to 5 parts by weight, preferably 1 to 3 parts by weight, more preferably 1.5 to 2.5 parts by weight, based on 100 parts by weight of the UV-curable adhesive composition.
[0075] In another embodiment, the UV-curable adhesive composition may contain 0.1 to 5 parts by weight, preferably 1 to 3 parts by weight, and more preferably 1.5 to 2.5 parts by weight of a photosensitizer, based on 100 parts by weight of the UV-curable adhesive composition.
[0076] In particular, the UV-curable adhesive composition according to the present application contains the cationic initiator in the above weight parts as described above, and the present application is characterized in that a radical monomer is used as the main material, but a cationic initiator other than a radical initiator is used. That is, when the UV-curable adhesive composition according to the present application contains a radical initiator, the adhesive strength is not good for both moisture-permeable and non-moisture-permeable substrates as in the present invention, and a decrease in adhesive strength occurs. The UV-curable adhesive composition according to the present application has the above composition and is characterized in that it exhibits excellent adhesive strength regardless of the substrate.
[0077] The present application provides an adhesive film comprising the UV-curable adhesive composition or a cured product thereof.
[0078] The method for producing the polarizing plate adhesive composition according to the present application is not particularly limited, and the composition can be obtained by mixing the above-mentioned components. In order to adjust the viscosity, an organic solvent may be appropriately used. There is also no particular limit to the mixing method, and the components may be sufficiently stirred and mixed at room temperature (20°C or higher and 25°C or lower) in a room that is shielded from UV light so as not to cause curing to proceed, until the liquid becomes uniform.
[0079] When applying the adhesive composition for a polarizing plate, it may be applied to either one of the transparent protective film or the polarizer, or to both.
[0080] The adhesive film may be laminated onto a substrate film during manufacture.
[0081] In one embodiment of the present application, said adhesive film may comprise the adhesive composition according to one embodiment of the present application as such.
[0082] In one embodiment of the present application, the adhesive film may include a cured product of the adhesive composition according to one embodiment of the present application.
[0083] In one embodiment of the present application, the substrate film may be selected from the group consisting of polyethylene terephthalate (PET), polyester, polycarbonate (PC), polyimide (PI), polyethylene naphthalate (PEN), polyether ether ketone (PEEK), polyarylate (PAR), polycycloolefin (PCO), polynorbornene, polyethersulphone (PES), and cycloolefin polymer (COP).
[0084] In another embodiment, the base film may be polyethylene terephthalate (PET).
[0085] In one embodiment of the present application, the thickness of the base film may be 10 μm or more and 200 μm or less, preferably 15 μm or more and 100 μm or less, and more preferably 20 μm or more and 75 μm or less.
[0086] The base film is preferably transparent, which means that the base film has a light transmittance of 80% or more for visible light (400 to 700 nm).
[0087] In one embodiment of the present application, an adhesive film is provided which further comprises a release film on one or both sides of said adhesive film.
[0088] In one embodiment of the present application, the adhesive film may have a thickness of 0.1 μm or more and 300 μm or less.
[0089] In another embodiment, the thickness of the adhesive film may be 0.1 μm or more and 100 μm or less, 0.1 μm or more and 80 μm or less, or 0.1 μm or more and 50 μm or less.
[0090] In one embodiment of the present specification, the thickness of the adhesive film is more than 0 μm and not more than 20 μm, more than 0 μm and not more than 10 μm, preferably about 0.1 μm to 10 μm or about 0.1 μm to 5 μm. When the thickness of the adhesive film satisfies the above range, the adhesive film has excellent uniformity and adhesive strength, and the apparent wrinkle phenomenon of the polarizing plate can be prevented.
[0091] The thickness of the adhesive film is not particularly limited by the method of applying the solid adhesive composition in the solution of the adhesive film, and various methods such as directly dropping the adhesive composition, roll coating, spraying, and immersion may be used.
[0092] In one embodiment of the present application, the adhesive film may have a surface energy of 35 mN / m or less.
[0093] In one embodiment of the present application, the adhesive film may have a surface water contact angle of 70° or more.
[0094] In one embodiment of the present application, the adhesive film may have a surface energy of 35 mN / m or less, a surface energy of 30 N / m or less, a surface energy of 25 mN / m or less, or may satisfy the surface energy range of 5 mN / m or more.
[0095] In one embodiment of the present application, the adhesive film may have a surface water contact angle of 70° or more, a surface water contact angle of 100° or more, a surface water contact angle of 110° or more, or a surface water contact angle of 180° or less.
[0096] According to one embodiment of the present application, the adhesive film satisfies the above surface water contact angle and surface energy, and the UV-curable adhesive composition contains a specific composition and content of monofunctional and polyfunctional acrylates, thereby satisfying the above ranges and having excellent wettability with the substrate.
[0097] In still another embodiment, a polarizer; a first adhesive layer and a second adhesive layer provided on both sides of the polarizer; 2 a transparent protective film having a moisture permeability of 150 g / m2 or less; and a second adhesive layer provided on the surface opposite to the surface in contact with the polarizer. 2 a transparent protective film having a shelf life of 24 hours or more; wherein the first adhesive layer and the second adhesive layer are the adhesive films according to the present application.
[0098] In one embodiment of the present application, the polarizing film can be produced by applying a UV adhesive composition onto the polarizer, and then bonding the polarizer and a transparent protective film by roll lamination or the like.
[0099] Specifically, after the bonding, the polarizing plate is irradiated with ultraviolet light to cure the adhesive composition. The source of ultraviolet light is not particularly limited, but a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a chemical lamp, a black light lamp, a microwave excited mercury lamp, a metal halide lamp, or the like, which has an emission distribution at a wavelength of 400 nm or less, may be used. The amount of ultraviolet light irradiation (accumulated light amount) is not particularly limited, but the amount of ultraviolet light irradiation in the wavelength region effective for activating the polymerization initiator is 100 mJ / cm. 2 More than 2,000mJ / cm 2 Within this range, the reaction time is suitable, and deterioration of the adhesive itself and the polarizing film due to heat radiated from the lamp and heat generated during polymerization can be prevented.
[0100] The polarizing film is stored at room temperature (20° C. or more and 25° C. or less, specifically, 25° C.) for 16 to 30 hours immediately after irradiation with ultraviolet rays. The polarizing film can be manufactured by completing the curing.
[0101] In one embodiment of the present application, the transparent protective film material is preferably a material excellent in transparency, mechanical strength, thermal stability, moisture blocking property, isotropy, etc. Examples of the material include cellulose resins such as cellulose diacetate and cellulose triacetate, polyester resins such as polyethylene terephthalate and polyethylene naphthalate, acrylic resins such as polymethyl methacrylate (PMMA), polystyrene resins such as polystyrene and acrylonitrile-styrene copolymer (AS resin), polycarbonate resins, polyolefin resins such as polyethylene, polypropylene, ethylene-propylene copolymer, and cycloolefin polymer, polyvinyl chloride resins, polyamide resins such as nylon and aromatic polyamide, polyimide resins, polysulfone resins, polyethersulfone resins, polyetheretherketone resins, polyphenylene sulfide resins, polyvinyl alcohol resins, polyvinylidene chloride resins, polyvinyl butyral resins, polyarylate resins, polyoxymethylene resins, epoxy resins, and blends of these resins.
[0102] In one embodiment of the present application, examples of the cellulose resin include cellulose triacetate (TAC), cellulose diacetate, cellulose tripropionate, and cellulose dipropionate. Among these, cellulose triacetate, cycloolefin polymer, polyethylene terephthalate, and acrylic resin are preferred from the viewpoint of availability and cost, and cycloolefin polymer, polyethylene terephthalate, and acrylic resin are more preferred from the viewpoint of availability and moisture permeability. If the protective film has high moisture permeability, moisture may penetrate the protective film and easily enter the polarizer side, which may deteriorate the quality of the polarizer.
[0103] A polarizer has a characteristic of being able to extract only light vibrating in one direction from incident light while vibrating in multiple directions. Such a characteristic can be achieved by stretching iodine-absorbed PVA (polyvinyl alcohol) with strong tension. For example, more specifically, a polarizer can be formed through a swelling step of immersing a PVA film in an aqueous solution to cause swelling, a step of dyeing the swollen PVA film with a dichroic material that imparts polarizing properties, a stretching step of stretching the dyed PVA film to align the dichroic dye material parallel to the stretching direction, and a complementary color step of correcting the color of the PVA film that has been stretched. However, the polarizing plate of the present invention is not limited thereto.
[0104] The polarizer may be a polarizer well known in the art, for example, a film made of polyvinyl alcohol (PVA) containing iodine or a dichroic dye. The polarizer may be manufactured by dyeing a polyvinyl alcohol-based film with iodine or a dichroic dye, but the manufacturing method is not particularly limited. The polarizing film refers to a state including a polarizer and a protective film.
[0105] The polarizer is manufactured through a process including a step of uniaxially stretching a polyvinyl alcohol-based resin film, a step of dyeing the polyvinyl alcohol-based resin film with a dichroic dye and allowing the dichroic dye to be adsorbed, a step of treating the polyvinyl alcohol-based resin film having the dichroic dye adsorbed thereon with an aqueous boric acid solution, a step of washing with water after the treatment with the aqueous boric acid solution, and a step of bonding a protective film to the uniaxially stretched polyvinyl alcohol-based resin film having the dichroic dye adsorbed and oriented after the above steps.
[0106] The uniaxial stretching may be performed before dyeing with a dichroic dye, simultaneously with dyeing with a dichroic dye, or after dyeing with a dichroic dye. When the uniaxial stretching is performed after dyeing with a dichroic dye, the uniaxial stretching may be performed before the boric acid treatment or during the boric acid treatment. It is also possible to perform the uniaxial stretching in these multiple steps. To perform the uniaxial stretching, the film may be uniaxially stretched between rolls having different peripheral speeds, or may be uniaxially stretched using a heated roll. The film may be dry-stretched in air, or wet-stretched in a state swollen with a solvent. The stretching ratio is not particularly limited, but is usually 4 to 8 times.
[0107] On the other hand, the polarizer preferably has a thickness of 5 μm to 40 μm, more preferably 5 μm to 25 μm. When the thickness of the polarizer satisfies the above numerical range, the polarizer has excellent optical properties, an appropriate amount of shrinkage at low temperatures, and excellent heat durability of the entire polarizing plate.
[0108] In addition, when the polarizer is a polyvinyl alcohol-based film, the polyvinyl alcohol-based film can be used without any particular limitation as long as it contains a polyvinyl alcohol resin or its derivative. In this case, the derivative of the polyvinyl alcohol resin can be, but is not limited to, a polyvinyl formal resin, a polyvinyl acetal resin, etc. In addition, a commercially available polyvinyl alcohol-based film, for example, P30, PE30, PE60 from Kuraray Co., Ltd., M2000, M3000, M6000 from Nippon Gosei Co., Ltd., etc., can be used, but is not limited to these.
[0109] The polyvinyl alcohol-based film preferably has a degree of polymerization of 1,000 to 10,000, more preferably 1,500 to 5,000. When the degree of polymerization is within the above range, the molecules move freely and can be flexibly mixed with iodine or a dichroic dye.
[0110] In one embodiment of the present application, there is provided a polarizing film, in which the adhesive strength of the surface of the first adhesive layer that contacts the polarizer and the adhesive strength of the surface of the second adhesive layer that contacts the polarizer are 150 gf / inch or more.
[0111] In yet another embodiment, there is provided a polarizing film, in which the adhesive strength of the surface of the first adhesive layer that contacts the polarizer and the adhesive strength of the surface of the second adhesive layer that contacts the polarizer are 150 gf / inch or more, preferably 200 gf / inch or more, and 600 gf / inch or less, more preferably 400 gf / inch or less.
[0112] The adhesive strength is expressed in units of gf / inch, but may also mean the same units as gf / 20 mm or gf / 25 mm.
[0113] That is, the polarizing film according to the present application has a first protective film on the top of the polarizer and a second protective film on the bottom of the polarizer. Even when a moisture-impermeable substrate is used on the top and a moisture-permeable substrate is used on the bottom, the polarizing film has excellent adhesive strength as described above because the UV curable adhesive composition has a predetermined composition and content.
[0114] FIG. 1 is a diagram showing a laminate structure of a polarizing film according to one embodiment of the present application. Specifically, a first adhesive layer 4 and a second adhesive layer 2 are provided on both sides of a polarizer 3, and a layer having a moisture permeability of 150 g / m 2 Transparent protective film for 24 hours or less, moisture permeability is 150g / m 2 -It can be confirmed that it contains 1 transparent protective film for at least 24 hours.
[0115] FIG. 1 is only one example and is not intended to limit the types of protective substrates that can be placed on the top and bottom of the polarizer.
[0116] In one embodiment of the present application, a polarizing film is provided, wherein the first adhesive layer and the second adhesive layer are the same.
[0117] That is, unlike the conventional method in which a moisture permeable substrate and a moisture non-permeable substrate are simultaneously used in a polarizer and different types of adhesive are used, the same type of adhesive layer is used, which provides excellent productivity of the polarizing film and prevents an increase in costs due to replacement of adhesives.
[0118] The adhesive composition for polarizing plates according to the present application may be suitably used for polarizing plates (polarizing films), retardation films, elliptically polarizing films, anti-reflection films, brightness enhancing films, indium-tin oxide sputtered transparent conductive films (ITO films), various electronics-related film members, protective films, etc. Among these, it is preferably used for polarizing plates (polarizing films).
[0119] Finally, there is provided a display device comprising the polarizing film of the present application. EXAMPLES
[0120] The present application will be described in more detail below using examples related to the present application and comparative examples not related to the present application, but the scope of the present application is not limited to the examples presented below.
[0121] <Experimental Example> UV adhesive compositions having the compositions and contents shown in Table 1 below were prepared.
[0122] Then, the UV adhesive composition was applied to both sides of a polarizer (manufactured by Nippon Gosei Co., Ltd.), and one side was coated with NRT TAC film (moisture permeability > 200 g / m 2 ·day) and the opposite is Toyobo Co., Ltd.'s PET (moisture permeability < 50g / m 2 After laminating the two layers, they were joined by roll lamination.
[0123] Thereafter, the polarizing plate was irradiated with ultraviolet light to cure the UV adhesive composition. The source of ultraviolet light was not particularly limited, but a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a chemical lamp, a black light lamp, a microwave excited mercury lamp, a metal halide lamp, or the like, which has an emission distribution of a wavelength of 400 nm or less, was used.
[0124] The irradiation dose (accumulated light amount) is 2000mJ / cm 2 The adhesive composition for polarizing plates was cured by irradiating ultraviolet light having a wavelength of 365 nm so that the polarizer and the protective film for release were bonded to each other, and the polarizing plate sample was manufactured by cutting the sample into a size of 2 cm wide x 15 cm long. At this time, the protective film for release was pretreated with KOH for each adhesive composition for polarizing plates.
[0125] The polarizing film was stored at room temperature (20°C to 25°C, specifically, 25°C) for 16 to 30 hours immediately after the UV irradiation. The polarizing film was obtained upon completion of curing.
[0126] [Table 1]
[0127] In Table 1, the numbers may refer to the parts contained in the entire adhesive composition (six types in Table 1). Also, DPGDA:50 in Example 6 means that 50 parts by weight of DPGDA was used instead of M210. Specifically, in Table 1, the numbers indicate the parts contained in each of the monofunctional acrylate, polyfunctional acrylate, and silane coupling agent monomers based on 100 parts by weight, and the cationic initiator, photosensitizer, and radical initiator are each indicated as parts contained in 100 parts by weight of the entire adhesive composition.
[0128] In this case, the monomer may further contain other additives, and the content of the additives is not included in Table 1 above.
[0129] In Table 1 above, DPGDA means dipropylene glycol diacrylate, 4-HBA (Osaka Chemical Industry Co., Ltd.) means 4-hydroxybutyl acrylate, and M210 (Bigen Shoji Co., Ltd.) means hydroxypivalic acid neopentylglycol diacrylate. Diacrylate), M370 (Bigen Shoji) tris(2-hydroxyethyl)isocyanurate triacrylate, KBM-403 (Shin-Etsu Chemical Co., Ltd.) 3-glycidoxypropyltrimethoxysilane, a substance having an epoxy group and at least one of the epoxy groups having an alicyclic epoxy group, KBM-503 (Shin-Etsu Chemical Co., Ltd.) 3-methacryloxypropyltrimethoxysilane, a substance having no epoxy group, KBM-5103 (Shin-Etsu Chemical Co., Ltd.) a substance having no epoxy group, Omnicat 250, (4-methylphenyl)[4-(2-methylpropyl)phenyl]-hexafluorophosphate(1-) in propylene carbonate, and DETX (IHT Co., Ltd.) 2,4-diethylthioxanthone were used.
[0130] The polarizing film produced as above was evaluated in the following Experimental Examples 1 to 4. The results are shown in Table 2.
[0131] [Table 2] <Experimental Example 1: Protective film peeling force experiment> The peeling protection film was peeled off at a peeling speed of 0.5 cm / sec for a distance of 3 cm or more, and the peeling force was measured three times and the average value was calculated. The peeling force was measured using an XT Plus Texture Analyzer (manufactured by TA Corporation).
[0132] At this time, the peel force (gf / 20mm) was evaluated as follows: ⊚ when it was 200gf / 20mm or more, O when it was 120gf / 20mm or more and less than 200gf / 20mm, Δ when it was 100gf / 20mm or more and less than 120gf / 20mm, and X when it was less than 100gf / 20mm.
[0133] <Experimental Example 2: Thermal shock evaluation> The polarizing film thus prepared was cut to a length of 150 mm in both the absorption axis direction and the direction perpendicular thereto. Then, an adhesive was applied to one side of the peelable protective film, which was then laminated onto a glass substrate and left at 25° C. for 24 hours.
[0134] The glass substrate was then left at -40°C for 30 minutes and at 85°C for 30 minutes, and this cycle was repeated 100 times. After the thermal shock was applied, the polarizer was observed from the edge of the polarizing plate in the stretching direction of the polarizer to see if there was any polarizer crack. If a crack was observed in the polarizer, the length of the crack was measured. If multiple cracks were observed, the average value was used for evaluation.
[0135] The test results were evaluated as follows: no cracks or cracks less than 1 mm long were marked with an ◎; cracks around 10 mm long were marked with an O; cracks around 50 mm long were marked with a Δ; and linear cracks occurring in bundles were marked with an X.
[0136] <Experimental Example 3: Hardening speed> The irradiation dose (accumulated light amount) is 2000mJ / cm 2 The adhesive composition for polarizing plates was cured by irradiating it with ultraviolet light having a wavelength of 365 nm so that the adhesive composition for polarizing plates became 100%. The protective film was immediately peeled off, and the cured coating film was rubbed with a hand to check whether the coating film was pressed or not.
[0137] Curing speeds of 10 seconds or less were rated as ⊚, those between 10 and 20 seconds as O, those between 20 and 50 seconds as Δ, and those over 50 seconds as X.
[0138] <Experimental Example 4: Written flattery> After fixing the protective film (TAC film), the adhesive composition was applied using a #3 bar. After 30 seconds, the film surface was checked for the occurrence of dewetting.
[0139] The case where the substrate had excellent wettability was indicated by ⊚, and the case where side shrinkage and circular dewetting occurred was indicated by X, and the evaluation was performed.
[0140] As can be seen from Table 2 above, the UV curable adhesive composition (Examples 1 to 7) according to one embodiment of the present invention necessarily contains a monofunctional acrylate, a polyfunctional acrylate, a silane coupling agent, a cationic initiator, and a photosensitizer. In particular, based on 100 parts by weight of the adhesive composition, the silane coupling agent contains 15 parts by weight or more of the silane coupling agent, the silane coupling agent has one or more epoxy groups in the molecule, at least one of the epoxy groups has an alicyclic epoxy group or a non-alicyclic epoxy group, and it has been confirmed that the adhesive composition has the characteristic of exhibiting excellent adhesive strength regardless of whether the substrate to be adhered is moisture permeable or non-moisture permeable.
[0141] As can be seen from the examples in Table 2, it was confirmed that Examples 1 to 7 having non-alicyclic epoxy showed particularly excellent results in the evaluation of peel strength and thermal shock resistance. This is because the non-alicyclic epoxy group is more excellent than the case where an alicyclic epoxy group is used in the initial feasilbility evaluation.
[0142] Furthermore, as can be seen from Examples 1 to 7, the polyfunctional acrylate contained in the film contains two types of acrylates, and among them, the acrylate containing two functional groups contains a specific content and specific functional groups, which can improve the wettability of the polarizing plate or substrate, and also has excellent adhesive strength regardless of the protective substrate used.
[0143] For reference, Examples 1 to 5 and 7 are cases where the acrylate containing two functional groups contains hydroxypivalic acid group, and Example 6 is a case where it does not. In this case, although there is a slight difference, it can be seen that there is a difference in adhesive strength to the TAC (NRT) substrate. In other words, it was confirmed that when the acrylate containing two functional groups contains hydroxypivalic acid group, the properties according to the present application are very excellent.
[0144] It has been confirmed that the UV curable adhesive composition according to one embodiment of the present invention contains a specific amount of monofunctional acrylate and polyfunctional acrylate, and reduces the surface energy of the adhesive layer containing the same, thereby preventing the generation of bubbles during processing, providing excellent wetting properties on a polarizing plate or substrate, and resulting in excellent appearance quality of a polarizing film containing the same.
[0145] Comparative Examples 1 to 4 in Table 2 above are cases where the monofunctional acrylate, polyfunctional acrylate, cationic initiator, or photosensitizer was not included, respectively, and as can be seen from the above experimental results, the adhesive strength was poor and the thermal shock resistance was also poor.
[0146] Comparative Examples 5 and 6 in Table 2 above contain a silane coupling agent but do not have an epoxy group as a functional group, and it was confirmed that the evaluations of the peel strength and thermal shock resistance were also poor.
[0147] The silane coupling agent according to the present application functions as an additive for increasing the adhesive strength of the composition in addition to its role as a normal coupling agent. However, in Comparative Examples 7 and 8, when the amount of the silane coupling agent was less than 15 parts by weight based on 100 parts by weight of the monomer, it was confirmed that the adhesive strength was not as good as that of the Examples.
[0148] Comparative Example 9 corresponds to a case where the amount of the (bifunctional) acrylate containing two functional groups is less than the range of the present application, and Comparative Example 10 corresponds to a case where the (bifunctional) acrylate containing two functional groups is not used. In the case of Comparative Example 9, the adhesive strength was measured to be higher than the other comparative examples, but it was confirmed that the adhesive strength was still poor compared to the examples. In addition, Comparative Example 10 corresponds to a case where one type of multifunctional acrylate was included. In this case, it was confirmed that the evaluation of the peel strength and the evaluation of the thermal shock resistance were also poor, as in the other comparative examples. [Explanation of symbols]
[0149] 1. Moisture permeability is 150g / m 2 Transparent protective film for 24 hours or more 2: Second adhesive layer 3. Polarizer 4. First adhesive layer 5. Moisture permeability is 150g / m 2 Transparent protective film for up to 24 hours
Claims
1. A UV-curable adhesive composition comprising a monofunctional acrylate, a multifunctional acrylate, a silane coupling agent, a cationic initiator, and a photosensitizer, The silane coupling agent is contained in an amount of 15 parts by weight or more based on 100 parts by weight of the monomer including the monofunctional acrylate, the polyfunctional acrylate, and the silane coupling agent, The polyfunctional acrylate includes an acrylate having two functional groups and an acrylate having three or more functional groups, The difunctional acrylate includes hydroxypivalic acid, Based on 100 parts by weight of the polyfunctional acrylate, the acrylate containing two functional groups is contained in an amount of 70 parts by weight or more, The UV-curable adhesive composition, wherein the silane coupling agent has one or more epoxy groups in the molecule, and at least one of the epoxy groups is an alicyclic epoxy group or a non-alicyclic epoxy group.
2. 2. The UV curable adhesive composition according to claim 1, comprising 1 part by weight or more and 30 parts by weight or less of the monofunctional acrylate and 40 parts by weight or more and 90 parts by weight or less of the polyfunctional acrylate, based on 100 parts by weight of the monomer.
3. 2. The UV-curable adhesive composition according to claim 1, comprising 0.1 to 5 parts by weight of the cationic initiator and 0.1 to 5 parts by weight of the photosensitizer, based on 100 parts by weight of the UV-curable adhesive composition.
4. The UV-curable adhesive composition according to claim 1 , wherein the functional groups of the monofunctional acrylate and the multifunctional acrylate are acrylate groups.
5. The UV-curable adhesive composition according to claim 1 , comprising 70 parts by weight or more and 80 parts by weight or less of the acrylate having two functional groups, based on 100 parts by weight of the multifunctional acrylate.
6. An adhesive film comprising the UV-curable adhesive composition according to any one of claims 1 to 5 or a cured product thereof.
7. The adhesive film of claim 6 further comprising a release film on one or both sides of the adhesive film.
8. The adhesive film according to claim 6 , wherein the adhesive film has a thickness of 0.1 μm or more and 300 μm or less.
9. Polarizer; a first adhesive layer and a second adhesive layer provided on both sides of the polarizer; The first adhesive layer has a moisture permeability of 150 g / m 2 - Transparent protective film for 24 hours or less; and The second adhesive layer has a moisture permeability of 150 g / m 2 ・Transparent protective film for 24 hours or more A polarizing film comprising: The polarizing film, wherein the first adhesive layer and the second adhesive layer are adhesive films according to claim 6 .
10. The polarized film according to claim 9 , wherein the adhesive strength of the surface of the first adhesive layer in contact with the polarizer and the adhesive strength of the surface of the second adhesive layer in contact with the polarizer are 150 gf / inch or more.
11. 10. The polarizing film of claim 9, wherein the first adhesive layer and the second adhesive layer are the same.
12. A display device comprising a polarizing film according to claim 9.
Citation Information
Patent Citations
Acrylic acid or methacrylic acid ester and diluent
JP1987108846A
Tacky tape and its production
JP2000073025A
Polarization film, manufacturing method thereof, optical film and image display unit
JP2015011094A
Active energy ray-curable adhesive composition, adhesive composition for polarizing plate, adhesive for polarizing plate, and polarizing plate prepared therewith
JP2018104635A
Adhesive composition for polarizing films, polarizing film, optical film and image display device
JP2018127610A